Preliminary study of local bentonite treatments for oil and gas industry - Samsuri, Ariffin; Abdullah, Habiburrohman; Leyong, Kien Ping (2001)
Bentonite was the first material used extensively as an additive in oil and gas industry especially in drilling mud and oilwell cement. In order to reduce the overall cost in oilwell drilling and completion, the development of local bentonite has been initiated. The samples of this study were taken from the areas of Lahad Datu and Tawau, Sabah, East Malaysia. As the local bentonite is not a sodium-based, a treatment method is sought to replace some of the ions on the unit clay surfaces with sodium ions. In this study, two methods were suggested for the purpose of ion exchange, the first being the wet method. In wet method, sodium carbonate, sodium bicarbonate or sodium chloride is used as the source of sodium ions. The process must be run in wet condition, that is either in solution form or in high moisture condition. The other method is the electrolysis process, in which an electric current will be used to perform the required ion exchange process. Before and after treatments, the local bentonite samples will be tested for physical and chemical properties, and mineral content to determine the optimum condition for the treatment processes, as per the API Specification 13A, 10A and OCMA requirements. Subsequently, tests will be run for the treated local bentonite in such applications as drilling mud (water-based mud), and oilwell cement slurry compare with the performance of commercial Wyoming bentonite.